Islands Education Studies and Challenges in Learning Science - Leasa, Marleny; Batlolona, John Rafafy; Jamaludin (Jurnal Penelitian dan Pengembangan Pendidikan, 2023)
Learning science in the archipelago has challenges and obstacles even though there has been a change in curriculum.  The problem in this study is how science is taught in the context of the KBK, KTSP and K-13 curricula. The aims of this research is to develop the curriculum from the KBK to the 2013 Curriculum in science learning. Qualitative research was carried out using case studies to check conditions through in-depth interviews with informants. The informants involved were teachers and principals at 17 elementary schools as well as the head of the local education office. Data collection was carried out through structured interviews with informants. The research instrument was an interview question sheet containing approximately 7 question items developed by the researcher based on the research objectives. Data analysis was carried out qualitatively through reduction, data display, and conclusion. The research findings show that 80% of informants prefer science learning to be managed separately from other lesson content. Although each curriculum has advantages and limitations. This is considered more effective in ensuring a broader and deeper understanding of the science concept. In addition, it was also revealed that the availability of facilities and teacher competence are factors that support the success of learning science in elementary schools. For future researchers, it is recommended that learning and curriculum be designed by showing partiality to subject matter and not combining one field of science with another.